KEARIFAN LOKAL DALAM TAFSIR TARJUMAN AL-MUSTAFID KARYA ABDUL RAUF AL-SINGKILI - Ida Novita; Halimatussa’diyah Halimatussa’diyah (Pascasarjana Universitas PTIQ Jakarta, 2023)
This study aims to explain: How is local wisdom in the book Tarjuman al-Mustafid by Abdul Rauf al-Singkili. This study used a descriptive method of analysis. The results showed that: Abdul Rauf Singkel the first tafsir scholar in the archipelago in the 17th century, evidenced by his tafsir work Tarjuman al-Mustafid. This Tafsir is written in full 30 Juz al-Qur'an with Malay Arabic script. In Abdul Rauf's interpretation in the book Tarjuman al-Mustafid found several elements of locality in it, such as the words syak, sail, kersa, rice, telekung, etc. So it can be said that there is a lot of local wisdom in the interpretation of this Tarjuman al-Mustafid book